ANALISIS PERAN ONLINE BRAND COMMUNITY DAN BRAND EXPERIENCE TERHADAP CUSTOMER ENGAGEMENT PADA FOLLOWERS AKUN INSTAGRAM BEAUTY PLATFORM DI INDONESIA - Tasya Kamila Wasita; Lili Adi Wibowo; lisnawati Lisnawati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2021)
The startup industry in Indonesia is growing, especially on platform that provide product information in the beauty sector. The number of customers who like beauty products, especially female customers at this time, has led to the emergence of several companies that create a beauty platform that provides information, reviews, and testimonials on various beauty products. Several Indonesian startup have succeeded in carrying out the strategy survive, demonstrate competitive advantage, and achieve customer engagement from consumers, but some have received little attention from the public, even had to go out of business because they couldn't compete with startup activists other. This study aims to determine the effect of online brand community and brand experience on customer engagement. The type of research used is descriptive verification, namely by describing and explaining the variables studied and then drawing conclusions. The dependent variables in this study are customer engagement (Y), online brand community (X1) and brand experience (X2) as independent variables. The population in this study are followers of the Instagram Female Daily Network, Beautynesia.id, and Story.id accounts. Sampling in this study used a simple random sampling method (random sampling) using a probability sampling technique of 200 account users. The analysis technique used is Structural Equation Modeling (SEM) analysis with IBM SPSS AMOS version 26.0 for Windows program tools. The findings of this study indicate that the description of online brand community and brand experience on customer engagement is in the good category. Online brand community and brand experience have a positive and significant influence on customer engagement.